1995
DOI: 10.1021/bi00027a004
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of a DNA Complex with the Fluorescent Bis-Intercalator TOTO Determined by NMR Spectroscopy

Abstract: We have used two-dimensional 1H NMR spectroscopy to determine the solution structure of the DNA oligonucleotide d(5'-CGCTAGCG-3')2 complexed with the bis-intercalating dye 1,1'-(4,4,8,8-tetramethyl-4,8-diazaundecamethylene)bis[4-(3-methyl -2,3- dihydrobenzo-1,3-thiazolyl-2-methylidene)qui nolinium] tetraiodide (TOTO). The determination of the structure was based on total relaxation matrix analysis of the NOESY cross-peak intensities using the program MARDIGRAS. Improved procedures to consider the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
167
2
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(198 citation statements)
references
References 41 publications
16
167
2
5
Order By: Relevance
“…These dimers consist of two identical fluorophores linked by a short flexible chain (EBEB (Ϸ1.54 nm), TOTO and YOYO (Ϸ1.68 nm)). The linker allows both dye groups to intercalate simultaneously in close proximity, generally 2 bp apart (16). It is consistent with our theory that such molecules should interact causing a significant decrease in polarization.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These dimers consist of two identical fluorophores linked by a short flexible chain (EBEB (Ϸ1.54 nm), TOTO and YOYO (Ϸ1.68 nm)). The linker allows both dye groups to intercalate simultaneously in close proximity, generally 2 bp apart (16). It is consistent with our theory that such molecules should interact causing a significant decrease in polarization.…”
Section: Discussionsupporting
confidence: 89%
“…At an incorporation density of 1:10, TO and YO will have on average two neighbors within energy transfer range in each direction. These molecules are held in a parallel orientation between the steps of the DNA ladder (16), further increasing the chance of dipole interactions. In contrast, at an incorporation density of 1:100, the average distance between dye molecules is 340 Å; well beyond the range of energy transfer for all dyes studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…generate forces as high as ∼60 pN. Also, structural studies of the DNA-YOYO-1 and DNA-TOTO complexes shows that this structure is more consistent with B than A form DNA (A form is 33% compressed compared with B), thus possibly accounting for comparable packaging inhibitory effects of 9AA and the more strongly binding YOYO-1 in our experiments (21,22). Overall, our direct FRET measurements showing likely DNA compression in the stalled Y-DNA stem and these results showing ID removal during translocation by the powerful motor appear to be consistent and confirmatory (8,10).…”
Section: Discussionsupporting
confidence: 66%
“…The suppression of the excitonic interaction is due not so much to the distance between the two chromophores in DNA as to their quasi-orthogonal relative orientation (NMR measurements of TOTO-1 bound to DNA indicate a dihedral angle 838 between the chromophoric units). [53] Indeed, it was demonstrated that the interaction between the chromophoric units is sufficient to allow high enough excitation energy to hop between the two chromophores within a few picoseconds. [39,41,54] Table 1.…”
Section: Resultsmentioning
confidence: 99%